Komplikasi Kronik Benda Asing pada Percabangan Bronkus - Russilawati Russilawati; Oea Khairsyaf (Jurnal Ilmu Kesehatan Indonesia, 2020)
CHRONIC COMPLICATION OF FOREIGN BODY IN TRACHEOBRONCHIAL TREE : A CASE REPORT Foreign body aspiration in tracheobronchial could be life threatening particularly if the object large enought to cause nearly complete obstruction. In the other hand small object could pass beyond carina and cause less severe sign and complication manifest. Chronic symptoms with recurrent infection that lead to brochiectasis may occur in delayed of extraction. We presented a case of nail aspiration by a 17 years old male patients who presented with hemoptysis. The patient had history of nail aspiration six months ago and had no symptom until the last one week . First attempt of evacuating used rigid bronchoscopy under general anesthesia had failed. Fiber optic bronchoscopy (FOB) found the nail at the orificium of right lower lobe and chest computed tomography stated the occurancy of bronchiectasis at distal of nail. The extraction was performed by FOB with local anesthesia succeeded to remove the nail to the laring that induced cough and nail threw out. There were no major complication and further symptoms after the extraction. Eventhough aspiration small object cause no symptom, it could lead to chronic complication such as bronchiectasis. FOB for removing the object is supposed to perform carefully because the object could fall on another part of brochial tree when it was pulled out. Keywords Foreign Body, Bronchial tree, complication, flexible bronchoscopy